EFFECT OF LEVEL OF COFFEE PRODUCTION ON THE PERFORMANCE OF COFFEE COOPERATIVE SOCIETIES IN KENYA - Maina, Irungu; Kiarie, Dr. David; Mugendi, Prof. Beatrice; Owaga, Dr. Eddy (European Journal of Business and Strategic Management, 2018)
Purpose: To evaluate the effect of level of coffee production on the performance of coffee cooperative societies in Kenya. Methodology: This study adopted a descriptive research design. The population of the study will be 1052 small holder coffee factories in Kenya. The research was done in the entire country which was divided into 18 strata from where 283 factories were sampled and studied. Results: The regression results revealed that level of coffee production had a positive and significant effect on performance of coffee cooperative societies in Kenya. Unique contribution to theory, practice and policy: The study recommends that the cooperative societies should work hard so as to improve the level of their coffee production. This will boost their performance.